Autophagy in neuronal physiology and disease. (October 2021) - Sumitomo, Akiko; Tomoda, Toshifumi
Abstract: Neural circuit functions critically depend on homeostatic regulation and quality control of neuronal proteins and organelles. Emerging evidence shows that autophagy, cellular clearance machinery, selectively degrades or controls homeostasis of both pre- and post-synaptic components (e.g. synaptic proteins, organelles, neurotransmitters, and their receptors), thereby regulating synaptic remodeling, neurotransmission, and neuroplasticity. Along with its well-known role in supporting neuronal cell viability and neurodevelopment, autophagy is now implicated in a wide range of neuronal physiology throughout neuronal lifetime, including higher-order brain functions such as information processing, memory encoding, or cognitive functions. Here, we review recent literature on the roles of neuronal autophagy in homeostatic maintenance of synaptic functions and discuss how disruptions in these processes may contribute to the pathophysiology of neurodevelopmental and psychiatric disorders.